Relationships between anhedonia, suicidal ideation and suicide attempts in a large sample of physicians. - Gwenolé Loas; Guillaume Lefebvre; Marianne Rotsaert; Yvon Englert (PLoS ONE, 2018)
The relationships between anhedonia and suicidal ideation or suicide attempts were explored in a large sample of physicians using the interpersonal psychological theory of suicide. We tested two hypotheses: firstly, that there is a significant relationship between anhedonia and suicidality and, secondly, that anhedonia could mediate the relationships between suicidal ideation or suicide attempts and thwarted belongingness or perceived burdensomeness.In a cross-sectional study, 557 physicians filled out several questionnaires measuring suicide risk, depression, using the abridged version of the Beck Depression Inventory (BDI-13), and demographic and job-related information. Ratings of anhedonia, perceived burdensomeness and thwarted belongingness were then extracted from the BDI-13 and the other questionnaires.Significant relationships were found between anhedonia and suicidal ideation or suicide attempts, even when significant variables or covariates were taken into account and, in particular, depressive symptoms. Mediation analyses showed significant partial or complete mediations, where anhedonia mediated the relationships between suicidal ideation (lifetime or recent) and perceived burdensomeness or thwarted belongingness. For suicide attempts, complete mediation was found only between anhedonia and thwarted belongingness. When the different components of anhedonia were taken into account, dissatisfaction-not the loss of interest or work inhibition-had significant relationships with suicidal ideation, whereas work inhibition had significant relationships with suicide attempts.Anhedonia and its component of dissatisfaction could be a risk factor for suicidal ideation and could mediate the relationship between suicidal ideation and perceived burdensomeness or thwarted belongingness in physicians. Dissatisfaction, in particular in the workplace, may be explored as a strong predictor of suicidal ideation in physicians.